2021
DOI: 10.1600/036364421x16231782047541
|View full text |Cite
|
Sign up to set email alerts
|

A New Distinctive Species ofSchizanthus(Solanaceae) and the Reinstatement ofSchizanthus fallax

Abstract: Abstract— A new Schizanthus species from northern Chile is described and illustrated. Schizanthus nutantiflorus was discovered based on recent collections made during unusual rain events in the Atacama Desert in 2015. The new species is distinguished morphologically from other Schizanthus species from northern Chile by its short corolla tube, with a distinct upper lip arrangement and colour, having the longest lower lip, and downward-facing flowers. Additionally, the reinstatement of Schizanthus fallax is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Specific status based on recent studies and reports published after April 2019 (not included in Palchetti et al, 2020 ) has been considered. This included studies, such as the revision of the genus Schizanthus ( Morales-Fierro et al, 2020 ; Lavandero et al, 2021 ); updates in Nolana ( Hepp and Dillon, 2018 ); the Morelloid clade of Solanum in Argentina ( Knapp et al, 2020 ); cryptic species recently reported ( Moreira-Muñoz and Muñoz-Schick, 2020 ); and new Petunia and Nicotiana species ( Greppi et al, 2019 ; Santilli et al, 2021 ). After a first cleaning, data from ex situ living collections that introduced species, hybrid taxa, and records with doubtful or incomplete identification at the species level were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Specific status based on recent studies and reports published after April 2019 (not included in Palchetti et al, 2020 ) has been considered. This included studies, such as the revision of the genus Schizanthus ( Morales-Fierro et al, 2020 ; Lavandero et al, 2021 ); updates in Nolana ( Hepp and Dillon, 2018 ); the Morelloid clade of Solanum in Argentina ( Knapp et al, 2020 ); cryptic species recently reported ( Moreira-Muñoz and Muñoz-Schick, 2020 ); and new Petunia and Nicotiana species ( Greppi et al, 2019 ; Santilli et al, 2021 ). After a first cleaning, data from ex situ living collections that introduced species, hybrid taxa, and records with doubtful or incomplete identification at the species level were excluded.…”
Section: Methodsmentioning
confidence: 99%